Profile of intraoperative complications in cataract surgery SEHEDS: Sitapur eye hospital eye disease study - Jaiswal, Nikita; Bhardwaj, Rahul; Tomar, Vijay Pratap Singh; Sharma, Sandeep; Kapoor, Niraj; Kohli, Anupriya; Siddiqui, Ruheen; Chaudhary, Prakhar (International Surgery Journal, 2020)
Background: Over the past several decades there have been many advances in the equipment, instrumentation and techniques of performing cataract surgery. This article will address the profile of intraoperative complications in cataract surgery. Methods: In this retrospective study all cataract procedures performed (n=18775) during the two years period (i.e. 2017 and 2018) were analysed and total 1401 (7.46%) valid cases (those having complications) were seen with 686 (49.0%) and 715 (51.0%) cases in the year 2017 and 2018 respectively. The age, gender, and side of the eye operated on were noted. The yearly incidence of the profile of complications was analysed. Results: Out of the total 1401 cases of eventful cataract surgery majority of the cases were of the age range of 51-70 years 1140 (6.07%) males were slightly higher in number i.e. 710 (3.78%) whereas females were 691 (3.68%), right eye was majorly operated for cataract i.e. 760 (4.05%). Manual small incision cataract surgery (MSICS) was done in the majority of the patients followed by phaco. The patients faced the complications due to cataract surgery in which posterior capsular rent- vitreous disturbance was the major complication occurred in majority of the patients 965 (5.15%). Conclusions: Patients who underwent eventful cataract surgery the most common intra-operative complications which were mainly posterior capsular rent- with vitreous disturbance and iridodialysis. Patients with higher risk factor should be identified and appropriate measures must be taken to minimize intraoperative complications to get better visual outcomes.